Unexpected Diagnosis of Both Adenocarcinoma of the Colon and Metastatic Lobular Carcinoma of the Breast in the Gastrointestinal Tract - Tegan Miller; Carol Ross; Haitham Al-Rawi; Barry Taylor; Mohammad Al-Jafari (Case Reports in Pathology)
Breast cancer rarely metastasises to the gastrointestinal tract. Lobular carcinoma more commonly metastasises to the uterus and appendages, peritoneum, and gastrointestinal tract than other types of breast cancer, while ductal carcinoma has a propensity to metastasise to the lungs, liver, and brain. We describe the case of a patient with no known history of breast cancer, whose primary presentation of lobular breast cancer was with malignant small intestinal and colonic strictures, with coexisting previously undiagnosed adenocarcinoma of the colon.